DIGITAL POSTER PROJECT AS AN ASSESSMENT IN EXTENSIVE READING CLASS - Erni Dewi Riyanti; Noorina Nyesti Rahmawati (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2021)
Indonesian teachers and students constantly cope with reading proficiency issues. As shown in related studies, students have inadequate opportunities to read materials that they are interested in; also, they deal with insufficient vocabulary and comprehension when they should read texts in English. Therefore, Extensive Reading (henceforth ER) is one of the solutions to enhance reading competence. This study was carried out qualitatively with a reflective teaching approach to examine the implementation of digital poster projects in Extensive Reading classes in the English Education Department, Universitas Islam Indonesia. The researchers record the application of the digital poster project. It is one of the class's reading projects and assigned individually and fully digital in the second half of the first semester. It also illustrates the class's general description, the process of the digital poster project conducted in class, the scoring rubric used, and students' opinions on the project. To gain further perspective, the researchers interview randomly selected students who provide their experiences throughout the class, responses on the digital poster project, strengths and weaknesses of the project, benefits gained from completing the project, and inputs for similar projects in the following year. The study believes that a digital poster project is advantageous; nevertheless, it requires better learning enhancement.